2003
DOI: 10.1007/s00122-003-1244-x
|View full text |Cite
|
Sign up to set email alerts
|

RFLP linkage analysis and mapping genes controlling the fatty acid profile of Brassica juncea using reciprocal DH populations

Abstract: An RFLP linkage map, comprising 300 linked and 16 unlinked loci, was constructed using reciprocal DH populations of Brassica juncea. The linked loci were organized into 18 linkage groups and seven unlinked segments, covering a total map distance of 1,564 cM. The A and B genomes were identified. The chi(2) test showed that 96.1% of the common intervals in the two populations differed non-significantly for recombination fractions, thus strongly suggesting the absence of sex-based differences for recombination fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Mukherjee et al (2001) identified two RAPD markers linked to the Albugo candida resistance locus which could be used in marker-assisted selection. Cheung et al (1998), Lionneton et al (2002) and Mahmood et al (2003a) mapped QTLs associated with the fatty acid profile in B. juncea. QTLs controlling aliphatic GSLs in mustard were mapped by Cheung et al (1998) and more recently by Mahmood et al (2003b).…”
Section: Introductionmentioning
confidence: 98%
“…Mukherjee et al (2001) identified two RAPD markers linked to the Albugo candida resistance locus which could be used in marker-assisted selection. Cheung et al (1998), Lionneton et al (2002) and Mahmood et al (2003a) mapped QTLs associated with the fatty acid profile in B. juncea. QTLs controlling aliphatic GSLs in mustard were mapped by Cheung et al (1998) and more recently by Mahmood et al (2003b).…”
Section: Introductionmentioning
confidence: 98%
“…NILs are particularly effective genetic stocks for studying phenotypic effects attributable to a QTL since the genetic background, including morphological and phenological characters that commonly influence phenotypic assessments of quantitative traits, is uniform. Double haploid (DH) populations have also been used for QTL mapping in several species (e.g., Bao et al 2002;Mahmood et al 2003;Behn et al 2005;Semagn et al 2006d;Semagn et al 2007;Xu and Crouch, 2008). The DH production methodology improves breeding efficiency by generating inbred lines with 100% purity and genetic uniformity in just two generations.…”
Section: The Genetic Dissection Of Quantitative Traits In Cropsmentioning
confidence: 99%
“…All F-tests in the mixed model were conducted using the appropriate mean squares for the error term according to Steel et al (1997). Generation means analyses (GMA) were conducted using regression analysis in SAS to estimate additive, dominance, and epistatic eVects as proposed by Hayman (1958) and Mather and Jinks (1971). The six generations used in the analysis included two non-segregating generations, P HE and P LE , and four segregating generations F 2 , F 3, BC 1 F 2 P LE , and BC 1 F 2 P HE .…”
Section: Discussionmentioning
confidence: 99%
“…Low erucic acid content is desirable in edible oils because high levels have adverse eVects on animal health (Beare et al 1963) and have been linked to growth inhibition and death when fed as a large proportion of animal diets (Thomasson and Boldingh 1955). Glucosinolates are sulfur-containing compounds that also cause health problems in animals (McKinnon and Bowland 1979). Improvement in seed and oil-processing techniques, combined with advances in plant breeding for oil quality, enabled canola oil to gain signiWcant market share as a cooking oil in the western hemisphere (Downey and R枚bbelen 1989).…”
Section: Introductionmentioning
confidence: 99%